Nonuniform Exponential Trichotomy for Linear Discrete-Time Systems in Banach Spaces - Xiao-qiu Song; Tian Yue; Dong-qing Li (Journal of Function Spaces and Applications)
The aim of this paper is to give several characterizations for nonuniform exponential trichotomy properties of linear difference equations in Banach spaces. Well-known results for exponential stability and exponential dichotomy are extended to the case of nonuniform exponential trichotomy.